Desenvolvimento de um sistema de liberação utilizando nanotubos de TiO2 - Dias, Lígia Cristina Camargo (Universidade Federal de São Carlos, 2020)
Titanium-based implants are being commonly used in the field of biomedicine due to their attractive biocompatibility and their mechanical properties that contribute to a better performance of the material. This dissertation develops a methodology for the synthesis of TiO2 nanotubes (NT's) applying it for the study in the controlled release of drugs. The previously polished Ti6Al4V alloy was used to form the nanotubular coating from potentiostatic anodization (25V / 90min) in a medium containing fluoride ions with the addition of a simulated body fluid solution (SBF), followed by a thermal treatment to form the phase anatase of TiO2. This system was used as a carrier system for the anti-inflammatory, one of the effects of the active pharmaceutical agent of the drug Ibuprofen. This drug was inserted in the nanotubes by the TopFilling method and its release was accompanied by visible ultraviolet spectroscopy (UV-Vis) for 7 days. Three types of samples were analyzed: Ti6Al4V polished (AT), after anodizing (ATA), and after anodizing and post heat treatment (ATT). Analyzes performed by scanning electron microscopy (SEM) of the nanotubes demonstrated that they have diameters between 54nm and 57nm. The anatase phase was confirmed by X-Ray Diffraction (XRD). Wettability was investigated through the contact angle, which showed contact angle values of 128.5° ± 0.8° for the AT sample, 78.4° ± 0.6° for the ATA, 16.4° ± 0.5° for ATT, indicating the variation in wettability depending on the type of treatment of the sample. It was observed in the release system a difference in the amount of initial and final concentration of Ibuprofen, in percentage, being possible to verify the difference in the release between samples, which alters the release kinetics as a function of time. The variation of the Ibuprofen release test points to the importance of surface treatment to delay the release of the drug, which can be an important factor in carrying drugs.
Development of a realese system using TiO2 nanotubes
Keywords: Biomaterias; Revestimento; Anodização; Nanotubos; sistema de liberação controlada.; Biomaterials; Coating; Anodizing; Nanotubes; Drug Release System.; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA; ENGENHARIAS::ENGENHARIA QUIMICA; ENGENHARIAS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::EXTRACAO E TRANSFORMACAO DE MATERIAIS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::DETERMINACAO DE ESTRUTURA DE COMPOSTOS INORGANICOS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA